Barriers and facilitators towards colonoscopy: a qualitative systematic review. Issue 3 (16th July 2020) - Lim, Kia Teng; Ng, Cheng Han; Decruz, Glenn Moses; Lim, Tian Zhi; Devi, Kamala; Tan, Ker-Kan; Chong, Choon Seng
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: Colonoscopy is integral in the early detection of colorectal cancer (CRC), be it for screening, diagnostic or therapeutic intentions. Despite the presence of multiple screening modalities, colonoscopy remains integral in providing a definitive CRC diagnosis. However, uptake rates remain low worldwide with minimal understanding towards stakeholders' perspectives. This systematic review is the first to outline the barriers and facilitators faced by providers and patients in receiving colonoscopy specifically. Methods: Using PRISMA guidelines, our systematic review consolidates findings from Medline, Embase, CINAHL, PsycINFO and Web of Science Core collection. All perceptions of healthcare providers and screening participants aged 45 and above towards colonoscopy were included. Results: Forty-five articles were included in our review. Five major analytical themes were identified – procedural perceptions, personal experiences, thoughts and concerns, societal influences, doctor-patient relationship and healthcare system. The discrepancies in knowledge between patients and providers have evidently reduced in the present decade, potentially attributable to the rising influence of social media. The sharing of providers' personal experiences, involvement of patients' family in colonoscopy recommendations and propagation of patients' positive recounts were also more apparent in the past compared to the present decade, highlighting the need to reevaluate the balance between medical confidentiality and personal touch. Additionally, Asian patients were reportedly more apathetic towards CRC diagnosis due to their strong belief in destiny, a crucial association consistent with present studies. Conclusion: This study highlights pertinent gaps in our healthcare system, providing crucial groundwork for interventions to be enacted in engendering higher colonoscopy uptake rates.